Understanding the potential of modern community center as social architectural spaces in Malaysia - Nangkula, Utaberta; Spalie, Nurhananie (Trans Tech Publications, 2015)
Malaysia is one of the classic examples of a multi-ethnic society. The country is proud of its multiracial culture which makes it a model for other countries. The ubiquitous community hall in the Malaysian landscape, as it stands now, has long passed its time of usefulness. These halls are labelled with names like dewan serbaguna, dewan orang ramai or even balai raya. But as it stands today, the community hall in our midst is nothing more than a large empty space used for games like badminton or ping pong and the occa-sional event. The changing modern Malaysian society demands more of this simple out-dated facility; there must be a place for the various ethnic groups to meet and fulfil modern needs such as family days, health checks, child’s play, music lessons and many more important uses This paper strives to identify and analyse some of the architectural problems in current community centres in Malaysia with the focus on the spatial aspects and space usage. It is expected that this paper can give a clear picture of the problems faced by Malaysian community centres with some considerations and a framework to develop a new scheme for community centre development in the future.